Exploring the critical role of binders in electrochemical CO2 reduction reactions - Chae, Younghyun; Kim, Hyunwook; Lee, Dong Ki; Lee, Ung; Won, Da Hye (Elsevier BV, 2024)
The electrochemical CO2 reduction reaction (CO2RR) has made significant progress as a carbon-neutral technology aimed at addressing the climate crisis. Advances in catalysts, membranes, and electrolyzers have propelled CO2RR systems to the techno-economic viability level. Although binders, which include ionomers and conducting polymers, are crucial components of these systems, their effects have been relatively underexplored. Traditionally, binders have been recognized as providers of physical stability and conductivity; however, their role extends beyond these functions. This review offers a comprehensive examination of the critical role of binders, including their impact on the overall electrode properties, the microenvironment of CO2RR, and their interactions with key reaction intermediates. We categorized the effects of binders into physical and chemical interactions and reviewed strategies for leveraging these effects in CO2RR applications. Additionally, we provide insights into the current challenges, future outlook, and development strategies for binders tailored to CO2RR needs.